2021
DOI: 10.1017/cjn.2021.146
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Movement Disorders: The Toxic Legacy Continues

Abstract: Mercury (Hg) exists in the environment as inorganic (metallic Hg vapor, mercurous and mercuric salts) or organic (bonded to a structure containing carbon atoms) forms. Neurotoxic effect of Hg is known for years. While the organic form (methylmercury (meHg)) led to the Minamata incidence in Japan and “wonder-wheat” disaster in Iraq, the “mad hatters” and “Danbury shakes” were related to the inorganic elemental form (Hg vapor). Human exposure to toxic Hg continues in the modern world to a large extent by artisan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Diseases like Minamata Disease, induced by methylmercury, specifically damage the central nervous system, distinguishing it from inorganic mercury poisoning, which primarily targets the kidneys. Despite these distinctions, mercury exposure has been associated with classic parkinsonian symptoms, including ataxia, tremors, and myoclonus [ 4 ]. Research indicates that mercury, in various chemical forms, exerts neurotoxic effects, contributing to neurochemical and neuropathological changes akin to those observed in Parkinson's disease [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diseases like Minamata Disease, induced by methylmercury, specifically damage the central nervous system, distinguishing it from inorganic mercury poisoning, which primarily targets the kidneys. Despite these distinctions, mercury exposure has been associated with classic parkinsonian symptoms, including ataxia, tremors, and myoclonus [ 4 ]. Research indicates that mercury, in various chemical forms, exerts neurotoxic effects, contributing to neurochemical and neuropathological changes akin to those observed in Parkinson's disease [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…There remains the remote possibility of mercury toxicity, a metal used in artisanal gold extraction, the most important economic activity in Vila Rica at that time. However, parkinsonism is not a complication of exposure to mercury 5 …”
Section: Figmentioning
confidence: 99%
“…However, parkinsonism is not a complication of exposure to mercury. 5 The old gentleman described in "Marília de Dirceu" may be the first person with parkinsonism, possibly caused by PD, described in the American continent. This case adds to the literature indicating that the shaking palsy is not a disease of the Industrial Revolution, with probable cases being reported in Asia, Europe and now, America.…”
mentioning
confidence: 99%
“…"Mercury (Hg), one of the representative heavy metals, is ranked third on the list of toxicological dangerous substances by the United States Toxicology and Disease Registry" [1]. "Hg is emitted into the environment from anthropogenic activities or natural sources" [2]. Anthropogenic actions such as inappropriate industrial waste management and illegal artisanal gold mining resulted in Hg contamination of ecosystems leading to the public health concern [3] caused by chronic exposure through the intake of food and water [4].…”
Section: Introductionmentioning
confidence: 99%